Probabilistic life-cycle seismic resilience assessment of aging bridge networks considering infrastructure upgrading. Issue 4 (2nd April 2020) - Capacci, Luca; Biondini, Fabio
Abstract: This paper presents a probabilistic framework for life-cycle seismic resilience assessment of aging bridges and transportation road networks subjected to infrastructure upgrade. The proposed framework accounts for the uncertainties in damage occurrence of vulnerable deteriorating bridges and restoration rapidity of the overall system functionality. The time-variant bridge fragilities and the damage combinations probability are evaluated considering different earthquake magnitudes and epicenter locations that define the seismic scenario. Traffic analyses are carried out to assess in probabilistic terms the network functionality profiles, the corresponding resilience levels, and a damage-based measure of life-cycle resilience. The effects of structural deterioration, seismic damage, and post-event repair actions under uncertainty are related to traffic restrictions applied over the network. The framework is applied to reinforced concrete bridges exposed to chloride-induced corrosion and simple road networks with a single bridge or two bridges in series under different earthquake scenarios. The effect of network upgrading is also investigated by adding road segments with a vulnerable bridge to strengthen the network connectivity and improve the lifetime system resilience. The results show the capability of the proposed resilience framework in quantifying the detrimental effects of structural deterioration at the network scale and the beneficial consequences of infrastructure investments, such as enhancing the network redundancy with the construction of an additional highway branch.